PENERAPAN METODE PEMBELAJARAN KOOPERATIF MODEL NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QURAN PADA SISWA KELAS V MI NURUL IKHLAS KP. PABUARAN DS. KEBONCAU KEC.PAMARAYAN KAB.SERANG - Sarbendi Sarbendi (STAI Darul Qalam Tangerang, 2025)
The learning model is felt to overcome learning problems. Not just providing knowledge or values or practicing skills but with education it is expected to be able to help students in developing the potential that students have towards positive change according to their abilities. The Application of the Numbered Head Together Model Cooperative Learning Model in Improving the Ability to Read the Quran in Students is one of the essential subjects for students not only containing knowledge that must be completed but must be carried out in daily life. This study aims to find out